Polycystic Ovarian Syndrome: Metabolic Challenge in Women (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
PCOS is a common and complex endocrine and metabolic disorder affecting women of reproductive age. It is characterized by a combination of menstrual irregularities, clinical or biochemical hyper androgenism, and polycystic ovarian morphology, with diagnosis commonly based on the Rotterdam criteria requiring two of these three features. PCOS is not only a reproductive disorder but also a multisystem condition associated with insulin resistance, obesity, dyslipidemia, impaired glucose tolerance, and increased long-term risk of type 2 diabetes and cardiovascular disease. It also contributes to infertility, acne, hirsutism, mood disorders, and reduced quality of life, making early recognition and holistic management essential. The pathophysiology of PCOS is multifactorial and includes genetic susceptibility, insulin resistance, hyperinsulinemia, altered ovarian steroidogenesis, and excess androgen production, while newer evidence also highlights the possible roles of gut microbiota, neuroendocrine dysfunction, and psychological factors. Diagnosis requires careful clinical assessment, exclusion of other androgen-excess disorders, and appropriate laboratory and ultrasound evaluation. Management is individualized and depends on the patient’s symptoms and reproductive goals. Lifestyle modification remains the foundation of treatment, especially in overweight and obese patients, while hormonal contraceptives are first-line therapy for menstrual irregularities, hirsutism, and acne in those not seeking pregnancy. For fertility management, ovulation induction is used, and metformin is beneficial for metabolic abnormalities and menstrual regulation. PCOS is increasingly recognized as a lifelong condition requiring patient education, regular screening, and multidisciplinary care. Awareness of its reproductive, metabolic, and psychological consequences is vital for improving outcomes and reducing future complications.
Keywords: Metabolism; Insulin resistance; Hormonal contraceptives; Endocrine disorder; Hyperandrogenism; Menstrual irregularities; Hirsutism Lifestyle modificatio; Ovulation induction